Determination of bed material transport with radioactive tracers - Hubbell, David Wellington, 1925-, author; Sayre, William W., 1927-, author; Colorado State University, publisher (Colorado State University. Libraries, 1963)
Since the advent of radioactive tracer techniques, application of Lagrangian experimental techniques in the investigation of sediment transport phenomena has become feasible. The results of one field experiment and two subsequent laboratory experiments in which radioactive tracer techniques were used to study the transport and longitudinal dispersion of bed-material particles is reported. The development of a concentration distribution function, which is based on a Lagrangian probabilistic model wherein the transport of bed material particles is described as a sequence of alternating steps and rest periods, and a method for determining the discharge of bed-material particles is reviewed. The discharge is obtained from applying the continuity principle to the mean rate of movement of a group of tracer particles and the effective cross sectional area of the bed through which they move. The concentration-distribution function and the method for determining bed-material discharge are examined in the light of the experimental data and are found to be applicable both in the field and in the laboratory.
CER63DWH-WWS16.
For presentation at ASCE Water Resources Engineering Conference, Milwaukee Wisconsin, May 13-17, 1963.
Keywords: Sediment transport; Radioactive tracers